Bimbingan Teknis Pidato (Tabibo) dalam Bahasa Gorontalo bagi Guru sebagai Pengajar Utama Revitalisasi Bahasa Daerah - Herman Didipu; Dodi Probowibowo; Putri Panggalih; Suci Wulandari (PT Cendekia Education Center, 2026)
The revitalization of regional languages is a strategic effort by the Indonesian government to preserve and develop regional languages, including the Gorontalo language which has been identified as needing increased usage. This community service article aims to describe the implementation, results, and impact of the Technical Guidance for Master Teachers of Regional Language Revitalization on speech (Tabibo) in the Gorontalo language for 160 teachers and representatives of the Education and Culture Offices throughout Gorontalo Province. The activity was carried out on Tuesday, March 3, 2026, from 13.00 to 16.30 WITA at Hotel Fox, Gorontalo City. The method used was a participatory training approach with three stages: pretest, provision of material through interactive lectures and group discussions, group practice of Tabibo speeches, and posttest. The instruments used were 20 multiple-choice questions, observation sheets, and reflection sheets. The results showed a significant increase in participants' understanding, with the number of participants in the very good category (85–100) increasing from 10 participants (6.25%) in the pretest to 90 participants (56.25%) in the posttest. The average score for Tabibo speech practice reached 86.2 (very good category). Participants also expressed a commitment to disseminate the training results to other teachers and students at their respective schools. This activity concludes that structured and participatory technical guidance is effective in improving teachers' competence in Tabibo speech and contributes to the revitalization of the Gorontalo language.